Evidence-Based Approaches to the Global Elimination of Trachoma: An Overview - Widarni (Journal of Health Science and Pharmacy, 2025)
Background: Trachoma is the third leading cause of blindness worldwide, after cataracts and glaucoma. It is responsible for visual impairment in approximately 1.9 million individuals globally, of whom around 1.4% experience total blindness. In Indonesia, the prevalence of trachoma as a cause of blindness is estimated at 0.98%. The disease is caused by infection with Chlamydia trachomatis. Objectives: This study aims to examine evidence-based strategies for trachoma control, encompassing medical, sanitation, and educational interventions, and to evaluate the effectiveness of global elimination programs. Methods: This study employed a literature review approach to identify and synthesize findings from relevant national and international journal articles. Sources were obtained from Google Scholar, PubMed, and ScienceDirect using the keywords Trachoma, Control, Chlamydia trachomatis, Blindness, and Elimination. The review included publications from 2010–2023 that addressed SAFE interventions Surgery, Antibiotics, Facial Hygiene, and Environmental Improvement. Results: Trachoma remains one of the leading causes of preventable blindness in developing countries and is classified among the seven neglected tropical diseases preventable through pharmaceutical interventions. The disease predominantly affects populations living in areas with limited access to clean water and adequate sanitation. It is estimated to cause visual impairment in approximately 2.2 million individuals worldwide, with around 1.2 million experiencing total blindness. Comprehensive implementation of the SAFE strategy has reduced trachoma prevalence by up to 70% in certain endemic regions. Mass administration of antibiotics (e.g., azithromycin), surgical management of trichiasis, promotion of facial hygiene, and improved access to clean water have demonstrated significant effectiveness. Nevertheless, challenges such as antibiotic resistance and limited resources continue to hinder elimination efforts. Conclusion: The primary strategy for trachoma control is the World Health Organization’s SAFE program, comprising Surgery, Antibiotics, Facial Hygiene, and Environmental Improvement. Effective control requires a multidisciplinary and sustainable approach. Strong collaboration among governments, international organizations, and communities is essential to achieving the global target of trachoma elimination by 2030. Keywords: Trachoma, Control, Chlamydia trachomatis, Blindness, Elimination